How mycorrhizas can help forests to cope with ongoing climate change? : Kako mikorize mogu pomoći šumama da se nose s aktualnim klimatskim promjenama - Milović, Marina (Array, 2021)
The ongoing climate change have multi-faceted effects not only on metabolism of plants, but also on the soil properties and mycorrhizal fungal community. Under climate change the stability of the entire forest ecosystems and the carbon balance depend to a large degree on the interactions between trees and mycorrhizal fungi. The main drivers of climate change are CO2 enrichment, temperature rise, altered precipitation patterns, increased N deposition, soil acidification and pollutants, ecosystem fragmentation and habitat loss, and biotic invasion. These drivers can impact mycorrhizal community directly and indirectly. We discussed the influence of each driver on mycorrhizal community and outlined how mycorrhizas play an important role in the resilience and recovery of forest ecosystems under climate change, by mitigating detrimental effects of CO2 enrichment, temperature rise, drought, lack of nutrients, soil acidification, pollutants, pests, and diseases. Conservation of the overall biodiversity in forest ecosystems as well as providing the most favourable conditions for the development of mycorrhizae can contribute to increasing the resilience of forest ecosystems to climate change.